'Like Romans Becoming Italians': Italy as the Negative Paradigm for British Decline in the Language of the Press and Denis Healey. Issue 1 (22nd March 2018) - Costa, Ettore
The article explores the views of Denis Healey about Italy, and demonstrates that his rhetoric on the Italian national character is connected to British socialism and the British relationship with Europe. Healey's opinions about Italy have been informed by the idea – very common among British and European socialists – that European people do not share a common nature. In 2013, he spoke of an 'olive line' separating the North – defined by pragmatism and responsibility – and the South – defined by abstraction and fiscal laxity. Healey adopted a discourse grounded in essentialism. Social and economic factors, contingency and agency are not important in shaping the behavior of a group of people. Political action is a derivative of the 'national character', a mixture of cultural and geographical determinism, which is hard to define and impossible to modify. This was used by Healey to explain the failure of democratic socialism in southern Europe. During the 1970s and 1980s, Italy played a part in Healey's reflections, and past experiences were reworked to validate his political positions. His argument about the national character formed the basis for his skeptical position regarding European unification, which in the 1970s had divided the Labour party, and worked against international socialist cooperation as well. Speaking about the 'national character' of the Italians was a rhetorical choice by Healey, which gained strength from pre-existing political positions from the early twentieth century, but could also be revitalised to deal with contemporary issues like the European Union and Britain's role in the world as late as 2013.